ANALISIS PENGELOLAAN SAMPAH BERDASARKAN KOMPOSISI SAMPAH PERUMAHAN DI WILAYAH SAMARINDA - Juli Nurdiana; Hana Fera Indriana; ika Meicahayanti (Mulawarman University Press, 2017)
ABSTRACT Purpose of this research are to analyze the proportion of waste composition, the obstacles in solid waste management at Samarinda and give the recomendation based on he proportion of waste composition, and the obstacles in solid waste management at Samarinda. Methods of waste collecting and measuring are cited on SNI 19-3964-1994 about Methods of Collecting and Measuring on Sample of Generated Urban Waste and its Composition, and method of collecting respondents data on each housing using accidental sampling method. From the research, the results have shown that waste composition of housing in Samarinda are food wastes 59,30% , plastics 17,90%, paper 12,93%, yard wastes 3,19%, cardboards 2,17%, diapers 2,04%, hazardous and poisonous waste 0,80%, tin cans 0,43%, glass 0,41%, wood 0,40%, textiles 0,28%, rubber 0,11%, metal 0,03% and leather 0%, meanwhile based on its variation are dominated by organic waste 62,90%, anorganic waste around 36,30% and hazardous and poisonous waste around 0,8%. Keywords: composition of solid waste, solid waste management, hazardous and poisonous waste, anorganic waste, organic waste